Barriers to antiretroviral adherence in HIV-positive patients receiving free medication in Kayunga, Uganda. - Senkomago, Virginia; Guwatudde, David; Breda, Mark; Khoshnood, Kaveh (AIDS care, 2011)
Global and local efforts have been devoted to increase the supply of antiretroviral therapy (ART) in sub-Saharan Africa. Recent qualitative studies suggest that even with free ART, patients may fail to adhere to medication because of socioeconomic barriers such as transportation costs to clinics. The aim of this study was to measure adherence in a population of patients receiving free ART and to examine barriers to adherence. Adherence was measured using the pill count and self-report methods among 140 HIV-positive patients at four PEPFAR-facilitated ART clinics in Kayunga, a rural district in Uganda. Self-report was also used to examine reasons for non-adherence. Pill count adherence estimates revealed that 86.4% of the patients were adherent (≥95%) in the past six months. Self-report estimates showed that all the patients were adherent in the past six months with average adherence of 99.7%±0.6. The main reasons for non-adherence were being away from medication at dose time (29.4%) and forgetting to take pills (27.5%). Lack of access to food and transportation costs accounted for 11.7% and 7.8% of non-adherence, respectively. Patients with 100% adherence reported lack of access to food as the main challenge they had to overcome to stay adherent. Patients attending the rural clinic were significantly less adherent to ART than patients at the Kayunga district capital [OR 0.046 (0.008-0.269)]. The study revealed that the greatest patient-perceived challenge to adherence in this population is the lack of access to food; however, the immediate reasons for non-adherence were found to be forgetfulness and being away from medication at dose's time. These results suggest that interventions tackling lack of access to food are necessary, but interventions addressing forgetfulness and being away from medication at dose's time would be the most effective in enhancing adherence inpatients receiving free ART.
Keywords: Adolescent; Adult; Aged; Anti-HIV Agents; Cross-Sectional Studies; Female; Health Services Accessibility; HIV Infections; Humans; Male; Medication Adherence; Middle Aged; Risk Factors; Rural Health; Self Report; Uganda; Young Adult